PENGARUH DESKRIPSI KERJA, JENJANG KARIR, MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. AGRINESIA RAYA MEDAN - Tambun, Erna; Tarigan , Miska Irani; Sitompul, Pandapotan; Tinambunan, Anitha Paulina (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to determine the effect of job descriptions, career paths and work motivation on employee performance at PT. Agrinesia Raya Medan. The research method used was quantitative, with a sample of 54 respondents participating, which was taken by purposive sampling. Data analysis in this study used SPSS version 25.00. The results of the t test show that partially job descriptions, career paths and work motivation have a positive and significant effect on employee performance. The F test shows that simultaneously job descriptions, career paths and work motivation have a positive and significant effect on employee performance. The coefficient of determination of 0.632 means that employee performance can be explained by job description, career path and work motivation variables of 63.2%, while the other 36.8% is explained by other variables not included in this study.